Comparison between autologous blood transfusion drainage and closed-suction drainage/no drainage in total knee arthroplasty: a meta-analysis - Hong, Kun-hao (BMC Musculoskelet Disord, 2016)
BACKGROUND: Autologous blood transfusion (ABT) drainage system is a new unwashed salvaged blood retransfusion system for total knee replacement (TKA). However, whether to use ABT drainage, closed-suction (CS) drainage or no drainage in TKA surgery remains controversial. This is the first meta-analysis to assess the clinical efficiency, safety and potential advantages regarding the use of ABT drains compared with closed-suction/no drainage. METHODS: PubMed, Embase, and the Cochrane Library were comprehensively searched in March 2015. Fifteen randomized controlled trials (RCTs) were identified and pooled for statistical analysis. The primary outcome evaluated was homologous blood transfusion rate. The secondary outcomes were post-operative haemoglobin on days 3–5, length of hospital stay and wound infections after TKA surgery. RESULTS: The pooled data included 1,721 patients and showed that patients in the ABT drainage group might benefit from lower blood transfusion rates (16.59 % and 37.47 %, OR: 0.28 [0.14, 0.55]; 13.05 % and 16.91 %, OR: 0.73 [0.47,1.13], respectively). Autologous blood transfusion drainage and closed-suction drainage/no drainage have similar clinical efficacy and safety with regard to post-operative haemoglobin on days 3–5, length of hospital stay and wound infections. CONCLUSIONS: Autologous blood transfusion drainage offers a safe and efficient alternative to CS/no drainage with a lower blood transfusion rate. Future large-volume high-quality RCTs with extensive follow-up will affirm and update this system review. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12891-016-0993-z) contains supplementary material, which is available to authorized users.